2013
DOI: 10.5539/jas.v5n5p57
|View full text |Cite
|
Sign up to set email alerts
|

Mapping New Genetic Markers Associated with CMD Resistance in Cassava (Manihot esculenta Crantz) Using Simple Sequence Repeat Markers

Abstract: Cassava mosaic disease (CMD) is the most serious disease in cassava-in India where it is grown for food, starch and sago purpose. The disease is best kept under control by exploiting the available host plant resistance, which was introgressed from M. glaziovii to cassava and it is known to be polygenic control. In the present study, an attempt was made to construct the genetic linkage map of cassava using SSR markers with the objective of mapping genes associated with CMD. Using single marker analysis (SMA), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…We confirmed that our major QTL is the CMD2 locus by aligning previously published SSR marker primers (SSRY28, NS158 and SSRY106) (Akano et al, 2002; Lokko et al, 2005; Okogbenin et al, 2007, 2012a; Mohan et al, 2013) to the reference genome using E-PCR (http://www.ncbi.nlm.nih.gov/tools/epcr/). Our significant markers on chromosome 8 co-locate with these markers (Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…We confirmed that our major QTL is the CMD2 locus by aligning previously published SSR marker primers (SSRY28, NS158 and SSRY106) (Akano et al, 2002; Lokko et al, 2005; Okogbenin et al, 2007, 2012a; Mohan et al, 2013) to the reference genome using E-PCR (http://www.ncbi.nlm.nih.gov/tools/epcr/). Our significant markers on chromosome 8 co-locate with these markers (Fig.…”
Section: Resultssupporting
confidence: 80%
“…More recently, a strong qualitative and dominant monogenic resistance known as CMD2 was discovered in a Nigerian landrace (TMEB3) in the 1980’s (Akano et al, 2002). Multiple bi-parental QTL analyses have been conducted, initially using SSR markers (Akano et al, 2002; Lokko et al, 2005; Okogbenin et al, 2007, 2012a; Mohan et al, 2013) but more recently genome-wide SNPs (Rabbi et al, 2014a; b) to understand the genetic basis of this type of qualitative resistance to CMD. Although some studies hint at additional resistance loci (Okogbenin et al, 2012a; Mohan et al, 2013) most evidence points solely to the CMD2 locus (Rabbi et al, 2014a; b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There were four significant markers on chromosome 14 with mostly dominant effects and explaining up to 5% of the variance. Two previously published SSR markers (SSRY44 and NS146) (Mohan et al, 2013) are located within 1.4 Mb of these SNPs (Supplemental Fig. S28b).…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of MAS depends on the proximity of the tag to the gene of interest, where distances are estimated by genetic recombination analysis. In fact, the distance between the NS158 × SSRY28 and NS158 × NS169 markers is relatively small, i.e., 2 cM (Mohan et al, 2013) and 9 cM (Fregene et al, 2006), respectively (Figure 1), which certainly contributes to providing a lower recombination rate between these markers. In addition, the NS158 and NS169 markers are anchored in Ribeiro et al (2012) identified 82 % of individuals with at least one allele for RME1, SSRY28 and NS158 markers, but only 62 subjects (28 %) had three allele markers that were associated with the CMD2 gene.…”
Section: Mas Implementation For Cmd Resistancementioning
confidence: 99%